2021
DOI: 10.31223/x5c890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D modeling of long-term slow slip events along the flat slab segment in the Guerrero Seismic Gap, Mexico

Abstract: • We model cycles of long-term slow slip events in the Guerrero Seismic Gap using a geometrically flexible 3D boundary integral method • Our model reproduces the source characteristics and surface deformation of four longterm SSEs inferred from geodetic observations • The flat segment of the Cocos plate likely aids the large magnitudes and long recurrence times of the slow slip events in Guerrero

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Liu and Rice (2007) showed that the fault response transitions from decaying oscillations to seismic events with increasing W / h *, with slow slip emerging in between the two. Likewise, previous models of SSEs in 2D (Liu & Rice, 2009) and 3D non‐planar faults (Li & Liu, 2016; Perez‐Silva et al., 2021) pointed out that the source properties of SSEs (e.g., slip rate, recurrence interval and magnitude) tend to positively correlate with changes in W / h *.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Liu and Rice (2007) showed that the fault response transitions from decaying oscillations to seismic events with increasing W / h *, with slow slip emerging in between the two. Likewise, previous models of SSEs in 2D (Liu & Rice, 2009) and 3D non‐planar faults (Li & Liu, 2016; Perez‐Silva et al., 2021) pointed out that the source properties of SSEs (e.g., slip rate, recurrence interval and magnitude) tend to positively correlate with changes in W / h *.…”
Section: Discussionmentioning
confidence: 76%
“…Given that the smallest value of the critical nucleation size ( h *) is 80 km, h */ dx ∼80, where dx is the average length of the triangle edges (1 km). Such discretization ensures that h * is well resolved, and is similar to that used in previous 3D simulations of SSEs (Li et al., 2018; Li & Liu, 2016, 2017; Perez‐Silva et al., 2021). We note that our model neglects normal stress changes induced by slip on the non‐planar fault, similar to previous SSE models in non‐planar faults (e.g., Li & Liu, 2016; Shibazaki et al., 2012, 2019).…”
Section: Model Setupmentioning
confidence: 87%
“…(2019) for work in this direction. With some exceptions (e.g., D. Li & Liu, 2017; Perez‐Silva et al., 2021; Sathiakumar et al., 2020) many studies focus on the already complex behavior of long‐term sequences of slip transients on linear or planar faults in simple domains.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no established method to construct meshes with time-dependent geometry and topology reflecting an evolving fault system, but we refer to K. Okubo et al (2019) for work in this direction. With some exceptions (e.g., D. Li & Liu, 2017;Perez-Silva et al, 2021;Sathiakumar et al, 2020) many studies focus on the already complex behavior of long-term sequences of slip transients on linear or planar faults in simple domains.…”
mentioning
confidence: 99%
“…A radiation damping term is included in the friction law to mimic the outflow of energy due to seismic waves (Rice 1993). SEAS models that neglect inertia and include radiation damping have been termed quasi-dynamic and can capture the period of stress accumulation and slow movements across faults (e.g., Rice 1993;Segall et al 2010;Perez-Silva et al 2021). Quasi-dynamic models quantitatively differ during the co-seismic phase in comparison to fullydynamic models (that include dynamic earthquake rupture) and it is under discussion under which circumstances the qualitative behaviour is affected (Thomas et al 2014).…”
Section: Introductionmentioning
confidence: 99%